Art as a Medium: Stróżewski and McLuhan on the Message and Mediating Nature of a Work of Art - Wesołowska-Starzec, Hanna (Roczniki Nauk Społecznych, 2025)
The aim of this article is to analytically compare two academic perspectives – the philosophical and the media-theoretical – specifically the aesthetics of Władysław Stróżewski and Marshall McLuhan’s concept of art. Stróżewski emphasizes the mediating function of the artwork as a carrier of values and meanings, while McLuhan sees works of art as specific forms of communicative media. Do these thinkers, rooted in different academic traditions, define the concept of art as a medium in a similar way? How does art as a medium affect the individual and culture? The methodology employed in this article is a comparative analysis of available literary sources. Despite their differing sources of inspiration, both scholars regard the artwork as a medium not only of meanings, but also of values and cultural messages. They also highlight the communicative, interactive, and transcendent character of art. A comparison of both approaches reveals a complementarity between their seemingly distant conceptions of art as a bearer of meaning and a medium of culture.